Konsep Zone Of Proximal Development (ZPD) Dalam Permainan Anak Anak - Ma'mun, Ahmad Aji Jauhari Ma'mun; Sri Handayani, Nungki; Munawarah, Hidayatu (Jurnal Tumbuh Kembang Anak Usia Dini, 2024)
The aim of this research is to explain the implementation of Vygotsky's zone of proximal development theory in children's play. This research uses library methods to analyze the research topics discussed. The results of this research found that Vygotsky did not discuss conceptually all types of games but only specialized in studying one type of game, namely sociodramatic or imaginative games. Sociodramatic games have 3 main characteristics that differentiate them from other games, namely a) imaginary situations, b) roles played and c) rules in the game. Imaginative play appears during the transition from infancy to toddlerhood as a result of the maturation of needs and motives for action. The play stage in ZPD considers two main factors, namely the assistance or participation given by adults to children and the child's initiative to play their own game. The play stage in ZPD is divided into several stages, namely a) Early Playing Age, b) Pre-School Age and c) School Age